Studying the effects of instance structure in algorithm performance - Turrubiates López, Tania; Schaeffer, Satu Elisa (2006)
the amount of resources consumed in the worst case. However, it has become evident that the instance size by itself is an insufficient measure and that the worst-case scenario is often unin-formative in practice. As a complementary analysis, we propose the examination of structural properties present in the instances and the effects they have on algorithm performance; our goal is to characterize complexity in terms of instance structure. We propose a framework for identifying and characterizing hard instances based on algorithm behaviour as well as a case study applying the framework on the graph coloring problem.